2000
DOI: 10.1136/gut.47.6.858
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic iron overload in aceruloplasminaemia

Abstract: We report the case of a 52 year old male with diabetes mellitus and long standing evidence of hepatic iron excess. Initially considered to have haemochromatosis, this patient was reevaluated when hepatic iron stores were found to be unaVected by a prolonged course of weekly phlebotomy. The development of neurological disease prompted diagnostic consideration of aceruloplasminaemia, which we confirmed by demonstration of a novel frameshift mutation in the ceruloplasmin gene. Our inability to resolve the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…LIC was strikingly elevated (535 mol/g dry weight [dw]; normal, 3-33) and hepatic iron index (LIC divided by years of age ϭ 8.6) was in the range observed in hereditary HFE. 18 However, common HFE mutations were negative. Rubeanic acid staining for copper was positive For personal use only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LIC was strikingly elevated (535 mol/g dry weight [dw]; normal, 3-33) and hepatic iron index (LIC divided by years of age ϭ 8.6) was in the range observed in hereditary HFE. 18 However, common HFE mutations were negative. Rubeanic acid staining for copper was positive For personal use only.…”
Section: Resultsmentioning
confidence: 99%
“…9 Aceruloplasminemia has been described mainly in Japanese patients [3][4][5][6][10][11][12][13][14][15][16][17] and rarely in whites. 5,18 We report data on a 62-year-old Italian woman, compound heterozygote for 2 novel mutations that hamper Cp expression in hepatocytes. Our findings suggest that the disorder should be considered in the differential diagnosis of anemia associated with unexplained iron overload.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review identified 32 published cases [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32]. Direct contact with the authors ascertained a further unpublished case.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of individuals and mice with congenital absence of Cp support a role for this protein in the removal of iron from Kupffer cells for redistribution to the body. 21,22 Previously, it has been shown that hephaestin is a copper-dependent oxidase protein that can rescue the low-growth phenotype of S cerevisiae ⌬fet3 strain in iron-poor media. 23 Moreover, we have shown that hephaestin is present in a supranuclear compartment and on the basolateral surface of intestinal enterocytes.…”
Section: Introductionmentioning
confidence: 99%